Penguatan Edukasi Akuntansi bagi Pelaku Usaha Mikro di Desa Sipayo: Strengthening Accounting Education for Micro Enterprises in Sipayo Village - Yusuf, Nilawaty; Niswatin, Niswatin; Hulopi, Titi Umi Kalsum (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Strengthening Accounting Education for Micro Enterprises in Sipayo village, realized through the KKN Thematic program, aims to increase MSME knowledge in calculating the Cost of Production and preparing simple financial reports. This activity was carried out because of the large number of MSMEs in Sipayo village who operate at the Sore market every day, and there was an expectation that the village head emphasized from the start for the community to be able to process their finances to become more structured. Community service activities consisting of pre-training, implementation, and evaluation stages provide results in the form of education on calculating the Cost of Production and recording simple financial reports, showing that most small business actors in Sipayo village rely more on memory accounting to carry out their business operations, so It is hoped that further community service activities will focus more on providing awareness and education that will convince the public to separate personal finance from their business.